Management of Compound Depressed Fractures over Venous Sinuses - Elbaroody, Mohammad; Marei, Ahmed A.; Sawy, Karim Fathy; Mahmoud, Alaa Eldin; Amin, Mark Charl; Elkatatny, Amr A.M.; badea, Hazem Abd Al (Asian Journal of Neurosurgery, 2024)
Objective The aim of this study was to report our experience in the surgical treatment of compound depressed fractures over the venous sinuses with special highlights on the prediction and dealing with intraoperative sinus injury.Materials and Methods We conducted a retrospective review of all patients who underwent surgery for compound depressed fractures overlying the dural venous sinuses in our hospital between January 2019 and December 2021.Results A total of 34 patients were included in our study. The mean age of the patients was 19.85 years, most of our patients were males 27 (79.4%), and isolated head trauma was the most common mode of trauma (76.5%). The superior sagittal sinus (SSS) was distinguished as the most commonly involved venous sinus below the fractures in 28 patients (82.4%). An intraoperative tear in the sinus was found in 17 patients (50%), which was easily controlled with different methods. In two patients who had a severe head injury with a Glasgow Coma Scale (GCS) score of ≤8 associated with a fissure fracture crossing the sinus, there was a complete tear of the sinus followed by massive bleeding, which required sinus ligation. We lost both of them in following days.Conclusion In experienced tertiary neurotrauma centers, compound depressed fractures over the venous sinuses should be surgically elevated in most cases, taking into consideration that bleeding from the sinus can be controlled in most cases, and complete tear of the sinus with massive bleeding is the least scenario faced in reality and is usually associated with a severe head injury. If expert opinion favors the conservative approach, then close follow-up for months is recommended due to the high possibility of sinus thrombosis and intracranial hypertension, especially in children.
Keywords: depressed; skull fracture; compound; open depressed fracture; sinus thrombosis; head injury; dural venous sinus